Trends and Dynamics of Indigene/Settler Conflicts in Plateau State, 1994-2010 - UMOH , Anthony Imeh; NWINKOL , Barinaadaa (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Plateau State is a vibrant mosaic of diverse ethnic, linguistic, and cultural communities. It boasts one of Nigeria's highest concentrations of ethnic minorities, with over fifty-eight distinct groups residing within its borders. Since Nigeria's return to democracy in 1999, the state has faced significant challenges in managing the complexities of indigene/settler dynamics and ethno-religious conflicts. While ethnic groups from various parts of Nigeria also live in Plateau State, the recurrent violent conflicts predominantly involve Hausa/Fulani settlers and the indigenous tribes. This paper delves into the patterns and intricacies of indigene/settler conflicts in Plateau State, analyzing their zero-sum nature where one group's gain is perceived as another's loss. It argues that the complexity of these conflicts is exacerbated by multiple interwoven factors, including ethnicity, religion, competition for scarce resources, and struggles for political and economic dominance. These factors collectively create a volatile environment, making conflict resolution particularly challenging. The study concludes that these persistent negative trends and dynamics have severely undermined the dividends of democracy in Plateau State. The ongoing conflicts have resulted in significant loss of life and property, leaving many homeless and exacerbating the socio-economic challenges faced by the state. This paper aims to shed light on the urgent need for comprehensive conflict management strategies to foster lasting peace and development in Plateau State.